(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aims to examine the role of implementing Total Quality Management (TQM) standards in achieving educational quality objectives. Education is a fundamental pillar in the development of societies. The research discusses the concept of TQM, its standards, and its impact on educational institutions in terms of improving academic performance, developing the learning environment, and enhancing the efficiency of teachers and administrators. The descriptive analytical approach was used to collect and analyze data from previous studies. The results indicated that applying TQM standards significantly contributes to improving the quality of education and enhancing institutional efficiency. The study recommends strengthening continuous training for educational professionals and adopting clear strategies to implement quality standards to ensure the achievement of educational goals.